Firm growth, European industry dynamics and domestic business cycles - Harald Oberhofer (FIW - Research Centre International Economics, 2010)
Based on the empirical firm growth literature and on heterogeneous (microeconomic) adjustment models, this paper empirically investigates the impact of European industry fluctuations and domestic business cycles on the growth performance of European firms. Since the implementation of the Single market program (SMP) the EU 27 member states share a common market. Accordingly, the European industry business cycle is expected to become a more influential predictor of European firms' behavior at the expense of domestic fluctuations. Empirically, the results of a two-part model for a sample of European manufacturing firms reject this hypothesis. Additionally, subsidiaries of Multinational Enterprises (MNEs) constitute the most stable firm cohort throughout the observed business cycle.
Keywords: F15; F23; L11; L16; L25; 330; Firm growth; industry dynamics; domestic business cycle; European integration; multinational enterprises; two-part model